(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
The achievements of the Road Map policy for the prevalence of Schisto Japonicum in Indonesia according to the target of 0% have not been achieved with the Schisto positive rate in 2022 still high. Schistosomiasis has social, psychological and public health impacts that impact people’s quality of life. There is a lack of synchronization in handling regarding prevention patterns, health maintenance, disease treatment, health restoration and protection of vulnerable people. This activity is the dissemination of research results using the PRA method to elements of society and RRA to officials for problem mapping. Empowerment through participation is expected to find a schistosomiasis management program that suits the capabilities and needs of relevant stakeholders. Empowerment in the Napu Valley involves traditional, religious, women, youth and farming community leaders. Apart from that, it also involves the sub-district head, village heads, Village Representative Body, hamlet heads, middle school, high school, vocational school principals, community health centers, supporting community health centers, as well as the Schisto Napu Laboratory. Empowerment uses a Logical Work frame to find the main problem which is the lack of awareness of the dangers of schisto due to economic needs and the absence of collaborative synergy between government-society and society in handling schisto. The planned activity program is intensity of age group-based socialization, social media-based socialization, formation of peer communities, irrigation arrangement, revitalization of mutual cooperation, construction of latrines in gardens around the focus and customary sanctions for those who violate, as well as awards for involvement innovation.